Kantor Sewa Di Dumai Dengan Pendekatan Eko-Arsitektur - Thandinifadio, Haqqi; Hidayat, Wahyu; Rijal, Muhammad (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Economic growth in Dumai City induce the business world characterized by the growth of industrial companies in the region. This affects the growth of the property sector, one of which is the increase in demand for office space and facilities. The Rent Office in Dumai is a means by which companies are directed against the run of office management to improve both the economic sector of the company itself as well as the economic territory of the Dumai city. In the design of the Rent Office, design approach emphasizes the design principles of eco-architecture with the aim of building a more designed to work together in an effort to notice the condition of the surrounding environment. But to direct more into the design of this specific concept then applied the concept of